Penerapan Filsafat Ilmu sebagai Landasan dalam Membangun Pendidikan Kritis dan Kreatif di SDN Rantau Pangeran - Suhud, Hary Kharisma; Susanti, Rahmi; Yosef, Yosef; Nawawi, Effendi (Asian Journal of Early Childhood and Elementary Education, 2024)
Education is not only about transferring knowledge, but also developing critical and creative thinking skills in students. One of the approaches that can be used to realize this goal is through the application of the philosophy of science in education, especially at the elementary school level. The purpose of this study is to understand how the principles of philosophy of science can be applied in the learning process in elementary schools, as well as to assess their impact on the development of students' critical and creative thinking skills. This study uses a qualitative approach with a case study method to explore the application of philosophy of science in building critical and creative education at SDN Rantau Pangeran. The results of this study show that the application of philosophy of science in learning at SDN Rantau Pangeran has had a significant positive impact on students' critical and creative thinking skills. Through this approach, students not only receive information passively, but are also invited to actively ask, analyze, and solve problems in a more in-depth way. The application of the philosophy of science successfully encourages students to think logically, systematically, and creatively, which is reflected in the improvement of their critical thinking skills and creativity which can be measured through tests and observations.